Antimicrobial Agents and Urinary Tract Infections - Issakhanian, Lernik; Behzadi, Payam (Current Pharmaceutical Design, 2019)
Urinary Tract Infections (UTIs); second-ranking infectious diseases are regarded as a significant global health care problem. The UTIs annually cost tens of millions of dollars for governments worldwide. The main reason behind these costs is incorrect or indefinite treatment. There are a wide range of gram-negative and grampositive bacteria which may cause UTIs in males and females, children and adults. Among gram-negative bacteria, some members of Enterobacteriaceae such as Escherichia coli (E.coli) strains have significant contribution in UTIs. Uropathogenic E.coli (UPEC) strains are recognized as typical bacterial agents for UTIs. Thus, sharp and accurate diagnostic tools are needed for detection and identification of the microbial causative agents of UTIs. In parallel with the utilization of suitable diagnostic methods-to reduce the number of UTIs, effective and definite treatment procedures are needed. Therefore, the prescription of accurate, specific and effective antibiotics and drugs may lead to a definite treatment. However, there are many cases related to UTIs which can be relapsed. Due to a diversity of opportunistic and pathogenic causative microbial agents of UTIs, the treatment procedures should be achieved by the related antimicrobial agents. In this review, common and effective antimicrobial agents which are often prescribed for UTIs caused by UPEC will be discussed. Moreover, we will have a sharp look at their (antimicrobials) molecular treatment mechanisms.
Keywords: antibiotics